THE PLASMA PHOSPHOLIPIDS EXCHANGE ON TO THE ERYTHROCYTE MEMBRANE LIPIDS: WITH DIFFERENT AGE GROUPS AND ANTI DIABETIC THERAPY. - BASAVARAJ ASKI; N.S.BIRADAR; S.S.WALVEKAR; KASHINATH R.T (International Journal of Pharma and Bio Sciences, 2014)
Dyslipideamia is a major cause, observed in type 2 diabetic subjects with micro vascular complications and membrane functional alteration is very common. The relative amount of phospholipids and cholesterol is responsible entity for normal function and membrane fluidity and rigidity. Many research studies reported on plasma lipid anomaly even on anti diabetic agents and also our earlier laboratory study supports, influence of anti diabetic therapy on plasma lipids and its relation to lipid alteration in erythrocyte membrane of diabetic subjects. Now effort has been made to rule out an anti diabetic effect on plasma phospholipids levels and its exchange on to the RBC membrane phospholipids composition of diabetic subjects with different age groups and anti diabetic therapy. Blood samples from randomly selected type-2 diabetic subjects were collected after obtaining written consent and institutional ethical clearance was obtained those who were attending Sri B.M. Patil medical college hospital for routine glycemic check up. The results of the study were statistically evaluated by Student‘t’ and Anova. The significant rise of Plasma and membrane TC, PL (P<0.001) at age of 45-55 years as compared to older age. On drug therapy, plasma and membrane TC, PL significant decrease (P<0.001) but ratio Increase, whereas on insulin treatment, plasma Glucose significantly decrease, But not much alteration of Plasma and membrane cholesterol However m PL P<0.001 Significantly Increase and m TC /m PL Ratio significantly decrease. Conclusion - In spite of treatment of diabetes, there is anomaly of lipid composition with age and anti diabetic therapy. Hence, the middle age group (45-55 years) diabetes subjects were more prone to risk of miro vascular complications than older age group (55 and above) and selection of anti diabetic treatment may play a significant role for glycemic control and Diabetic complications .